Impact of Probiotics on Dairy Production Efficiency - Nalla, Kirankumar; Manda, Naresh Kumar; Dhillon, Harmeet Singh; Kanade, Santosh R.; Rokana, Namita; Hess, Matthias; Puniya, Anil Kumar (Frontiers in Microbiology, 2022)
Probiotics are the natural bio-therapeutics that increasingly gain stakeholders' interest for innovative management of dairying systems. These beneficial growth promoters enhance weight gain and disease resistance in young calves whereas, improve the milk yield in lactating animals. Oral administration of probiotic-based feed additives could reduce the negative energy balance during the peak lactation period. The exact way of beneficial action of probiotics is not completely understood yet, but their ability to modulate the gastrointestinal microbial community is proposed as the main approach. The establishment of probiotic-mediated microbial homeostasis in rumen could improve feed conversation competence, volatile fatty acid production and nitrogen flow that enhances the milk composition as well as milk production. Moreover, as living bio-therapeutic agents, probiotics have the potential to directly change the gene expression profile of animals by activating the signalling cascade in the host cells. Various direct and indirect components of probiotic approaches to improve the productivity of dairy animals are discussed in this review.